Successful Management of a Patient with Intraoperative Bleeding of More than 80,000 mL and Usefulness of QTc Monitoring for Calcium Correction - Yuki Sugiyama; Kazuma Aiba; Nariaki Arai; Mariko Ito; Masatoshi Urasawa; Chie Hirose; Ikuko Murakami; Ryusuke Tanaka; Tomokatsu Yamada; Keisuke Iida; Hiroyuki Nakamura; Mikito Kawamata (Case Reports in Anesthesiology)
Intraoperative massive bleeding is associated with high rates of mortality and anesthetic management of massive bleeding is challenging because it is necessary to achieve volume resuscitation and electrolyte correction simultaneously during massive transfusion. We report a case of life-threatening bleeding of more than 80,000 mL during liver transplantation in which real-time QTc monitoring was useful for an extremely large amount of calcium administration for treatment of hypocalcemia. A 47-year-old female with a giant liver due to polycystic liver disease was scheduled to undergo liver transplantation. During surgery, life-threatening massive bleeding occurred. The maximum rate of blood loss was approximately 15,000 mL/hr and the total amount of estimated blood loss was 81,600 mL. It was extremely difficult to maintain blood pressure and a risk of cardiac arrest continued due to hypotension. In addition, even though administration of insulin and calcium was performed, electrolyte disturbances of hyperkalemia and hypocalcemia with prolongation of QTc interval occurred. At that time, we visually noticed that the QT interval was shortened in response to bolus calcium administration, and we used the change of real-time QTc interval as a supportive indicator for calcium correction. This monitoring allowed for us to administer calcium at an unusually high rate, by which progression of hypocalcemia was prevented. Levels of hemoglobin and coagulation factors were preserved both by restriction of crystalloid infusion and by a massive transfusion protocol. The patient was extubated without pulmonary edema or cardiac overload and was finally discharged without any sequelae. Intensive and cooperative management for massive transfusion and electrolyte correction using QTc monitoring was considered to be a key for successful management.